Evaluation Of Branch Achievement Development Of Wrestling, Weightlifting, and Athletic Koni Bengkulu Province - Tono Sugihartono; Santun Sihombing; Anggi Wijaya Kusuma (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine the achievement of coaching achievements in the sports of Wrestling, Weightlifting, and Athletics KONI Bengkulu. The type of research used in this research is descriptive qualitative research with a CIPP evaluation research approach. The research subjects were 3 sports, totaling 48 people consisting of 3 coaches, 10 athletes, 3 athletes. Instruments and data collection techniques using observation techniques, questionnaires and documentation. The data analysis technique used is descriptive analysis with percentages. The results of the study are the results of the evaluation of observations both from the monitoring process, the training process, and the condition of the infrastructure. The results of the evaluation stated that the percentage of questionnaires on the achievement development of wrestling, weightlifting and athletics at KONI Bengkulu Province, the average assessment showed the context component was in the "very good" category with a percentage (95%), the input component was in the "very good" category. with a percentage (94%), the process component is in the "Excellent" category with a percentage (83%), and the product component is in the "Good" category with a percentage (91%), the achievement of wrestling shows consistency compared to lifting sports iron, but in the Athletics show an increase. Based on the results of the study, it can be concluded that the Development of Achievements in Wrestling, Weightlifting, and Athletics is in the good category.